To determine if \( x = -3 \) is a solution to the quadratic equation \(-3x^2 - 9x = 0\), we need to substitute \( x = -3 \) into the equation and see if it results in a true statement.
The equation is: \[ -3x^2 - 9x = 0 \]
Substituting \( x = -3 \):
\[ -3(-3)^2 - 9(-3) = 0 \]
Calculating:
- First, compute \((-3)^2 = 9\).
- Then, compute \(-3(9) = -27\).
- Next, compute \(-9(-3) = 27\).
Putting it all together: \[ -27 + 27 = 0 \]
Thus, we have: \[ 0 = 0 \]
This is a true statement. Therefore, the correct explanation is:
Yes, \( x = -3 \) is a solution because substituting it back into the equation results in the following: \[ -3(-3)^2 - 9(-3) = 0 \quad \Rightarrow \quad 0 = 0 \quad \text{(True)} \]